Mendialogkan Peradaban Timur-Islam dan Barat-Kristen - Asna Andriani (Institut Ilmu Keislaman Annuqayah, 2015)
During this time the meaning of West and Islam are so strongly attached into a kind of stereotype for both. The emergence of certain assumptions about both sparked problems. Thus need for dialogue between the two civilizations which aims to break down misunderstandings, because basically in the existence of Western civilization-Christian, there is the role of Eastern civilization-Islam is very large, and vice versa in the formation of Eastern civilization-Islam, Christians also have a very vital role. So, both have relationships need each other. This paper seeks to provide a discourse of dialogue between the civilizations of East-Islam and Western-Christian, while reconstructing the new identity of Islamic civilization-Western, hoping to contribute to the realization of global civilization, world peace without destructive conflict and war.